O ciclo de crescimento de Goodwin e a parcela salarial na economia brasileira - Miebach, Alessandro Donadio (2017)
This study analyzes the presence of the Goodwin growth cycle (or Goodwin model) in the Brazilian economy for the period between 1947 and 2013. The analysis is carried out through a wage share time series obtained from the sources from the Brazilian economy and a series for the level of capacity utilization. Obtaining wage share time series contemplates the division of mixed incomes between labor income and capital income. The analysis for the presence of Goodwin cycles is made through a qualitative evaluation, the procedures of Harvie (2000) and Pichardo (2015). In addition, dummy variables are used to identify the dynamics between the wage share and the level of capacity utilization corresponding to different periods in the history of the Brazilian economy. The periods are defined according to the current socioeconomic characteristics of Brazilian society. The results indicate the presence of mechanisms of the type associated with the Goodwin model for different moments in the Brazilian economy. However, the Goodwin cycle is only observed for the period between 1998 and 2009.